In Situ Formed Ag‐Li Intermetallic Layer for Stable Cycling of All‐Solid‐State Lithium Batteries (Adv. Sci. 1/2022). Issue 1 (5th January 2022) - Choi, Hong Jun; Kang, Dong Woo; Park, Jun‐Woo; Park, Jun‐Ho; Lee, Yoo‐Jin; Ha, Yoon‐Cheol; Lee, Sang‐Min; Yoon, Seog Young; Kim, Byung Gon
Abstract : All‐Solid‐State Lithium Batteries In article number 2103826, Seog Young Yoon, Byung Gon Kim, and co‐workers introduce the cell incorporating Ag‐Li alloy anode fabricated via mass‐producible roll pressing method. It shows better cycling and rate performances compared to the cell with metallic Li anode, owing to the in situ formed Ag‐Li intermetallic layer physically controlling uneven Li deposition and chemically forming a stable solid electrolyte/anode interface.